The Origin of Excellent Gate‐Bias Stress Stability in Organic Field‐Effect Transistors Employing Fluorinated‐Polymer Gate Dielectrics. (29th September 2014) - Kim, Jiye; Jang, Jaeyoung; Kim, Kyunghun; Kim, Haekyoung; Kim, Se Hyun; Park, Chan Eon
<x xml:space="preserve">Abstract</x> Tuning of the energetic barriers to charge transfer at the semiconductor/dielectric interface in organic field‐effect transistors (OFETs) is achieved by varying the dielectric functionality. Based on this, the correlation between the magnitude of the energy barrier and the gate‐bias stress stability of the OFETs is demonstrated, and the origin of the excellent device stability of OFETs employing fluorinated dielectrics is revealed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>